A reinforced Pickering emulsion for cascade reactions. Issue 92 (5th November 2018) - Xue, Nan; Zhang, Gaihong; Zhang, Xiaoming; Yang, Hengquan
Abstract : Based on an interfacial sol–gel process, a novel reinforced Pickering emulsion has been developed successfully for one-pot cascade reactions involving incompatible catalysts. Abstract : Based on an interfacial sol–gel process, a novel reinforced Pickering emulsion has been developed successfully for one-pot cascade reactions involving incompatible catalysts.